CUSHING’S DISEASE AND THROMBOSIS: A CLINICAL PERSPECTIVE - L, Fion; M, Saieehwaran; R, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Cushing’s disease is the most common cause of endogenous Cushing’s syndrome, which is caused by an adrenocorticotropin (ACTH) -secreting pituitary tumour. It poses a myriad of complications due to the state of excess cortisol levels, including thrombosis. It is interesting that thrombotic risk due to the hypercoagulable state in Cushing's disease is higher after pituitary surgery when cortisol levels are diminished. We present a case of a female with recurrent Cushing's disease who developed extensive thrombotic complications post-successful transsphenoidal surgery (TSS) to highlight the importance of anticoagulation therapy in mitigating the risk of thrombosis. CASE A 31-year-old female with underlying diabetes mellitus, hypertension and a history of previous treatment for Cushing’s disease presented with symptoms of weight gain, hirsutism and purplish striae for 2 years. MRI showed a pituitary adenoma measuring 2.8x4.4x3.3 mm. A 24-hour urinary cortisol and overnight dexamethasone suppression tests were not suppressed. She underwent endoscopic TSS. Post-surgery, her cortisol levels reduced from 419 to 57.3 nmol. Subsequently, she was found to have a saddle pulmonary embolism and extensive right lower limb deep vein thrombosis requiring pulmonary thrombectomy. Post-procedure, she was started on anticoagulants. Hypercoagulation in Cushing's disease is due to the increase in clotting factors II, V, IX, and VIII, fast-acting plasminogen activator inhibitors and the decrease of tissue-type plasminogen. The stress post-surgery causes an abnormal Von Willebrand Factor pattern production leading to platelet aggregation and the drop in cortisol levels will trigger an inflammatory response that initiates the coagulation cascade. The elevated thrombotic risk will decrease after 3 months to a year later as the glucocorticoid effect takes time to wean off, hence requiring anticoagulation. CONCLUSION Recognition of thrombosis post-surgery for Cushing’s disease is vital to prevent mortality and morbidity. An individualized strategy based on the degree of thrombosis is therefore essential in the management.